Analisis Buku Teks Bahasa Indonesia SMA Kelas X Ditinjau dari Aspek Kesesuaian Materi Ajar dengan Kurikulum - Mazhud, Nurfathana (Fakultas Sastra Universitas Muslim Indonesia, 2024)
A teacher conveys various learning materials, of course, still referring to the learning resources used by the school. Learning resources that can be used in the process of learning activities at school are very varied, one of which is textbooks. This study aims to describe the analysis of the suitability of the material with the curriculum by focusing on the competencies in the curriculum of Indonesian Language subjects. Therefore, the researcher will analyze the Indonesian Language textbook published by the Ministry of Education and Culture in the latest revised edition in 2017 for high school class X. The design used in this study is a qualitative descriptive research design. In the application of this research design, the author collects data on the description of learning materials in the Indonesian Language textbook for class X, processes, and then analyzes the data on the suitability of material aspects with the curriculum. To test the data that has been analyzed, the researcher conducted a data triangulation examination and source triangulation. The results of the study show that the description of the material of each chapter has basically presented completely based on the indicators that must be achieved. The feasibility of describing the content of the material in the Indonesian Language book for class X from themes 1-8 has met the criteria for completeness of the content, namely the material described to support the achievement of core competencies (KI) and basic competencies (KD). The presentation of the material in this book refers to the revised 2013 curriculum, which uses texts in the context of developing student competencies.